HUBUNGAN KEMAMPUAN SISWA DALAM MENGIDENTIFIKASI KEBERAGAMAN SUKU, AGAMA, RAS, DAN ANTARGOLONGAN DALAM BINGKAI BHINNEKA TUNGGAL IKA DENGAN SIKAP MENGHARGAI KEBERAGAMAN SUKU, AGAMA, RAS, DAN ANTARGOLONGAN (STUDI SISWA KELAS VII SMP NEGERI 4 SURAKARTA) - Wahyuningsih, Ika; Suryono, Hassan; Rasyid, Machmud Al (PKn Progresif : Jurnal Pemikiran dan Penelitian Kewarganegaraan, 2018)
The purpose of this study was to determine the relationship between students' ability in identifying ethnic, religious, racial and intergroup diversity in the frame of Unity in Diversity with an attitude of respect for ethnic, religious, racial and intergroup diversity in class VII students of Surakarta State Junior High School 4.This research is quantitative research. The method used is descriptive correlational statistics. Subjects in this study were class VII students of SMP Negeri 4 Surakarta using simple random sampling technique. Data collection techniques used are test and questionnaire instruments. Validity test used uses the product moment formula. Reliability testing uses the Spearman Brown formula to test the X variable, and the Cronbach Alpha formula to test the Y variable. Data analysis uses a simple correlation technique.The results in this study are that there is a positive and significant relationship between students' ability to identify ethnic, religious, racial and intergroup diversity in the frame of Unity in Diversity with an attitude of respect for ethnic, religious, racial and intergroup diversity. A positive relationship between variable X and variable Y is indicated by the value of r count = 0.889> r table = 0.244. The meaning of the relationship between variable X and variable Y is significant indicated by the value of t count = 15, 28> t table1.27. Keywords: identifying diversity, respect.